2018
DOI: 10.1097/jcn.0000000000000525
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Younger Individuals Living With Heart Failure

Abstract: Background: Heart failure (HF) impacts 1.7 million Americans between the ages of 20 and 59 years, but limited research exists addressing the issues unique to this age group. Objective: The aim of this study was to investigate the experiences of younger persons living with HF. Methods: Semistructured interviews (n = 18) were analyzed using a qualitative thematic analysis. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Results showed that the intervention group had a decrease in fatigue and an improvement of QoL, whereas no significant changes were observed in the control group. Similarly, an exercise program significantly improves fatigue and QoL from baseline to 12 weeks later [41].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the intervention group had a decrease in fatigue and an improvement of QoL, whereas no significant changes were observed in the control group. Similarly, an exercise program significantly improves fatigue and QoL from baseline to 12 weeks later [41].…”
Section: Discussionmentioning
confidence: 99%
“…Running Out of Batteries Bad Life Associated Symptoms Feeling Misunderstood HF Dickson et al 17 A A Gwaltney et al 18 A A A Hagglund et al 15 A A A A Holden et al 20 A A A Jones et al 23 A A A A Jurgens et al 19 A A A A Norberg et al 21 A A A A Walsh et al 22 A A A A MS Al-Sharman et al 24 A A A A Kayes et al 12 A A A Lohne et al 11 A A A A Moriya and Kutsumi 25 A A A A Newland et al 26 A A A A Barlow et al 27 A A A A Turpin et al 28 A A A A RA Connolly et al 29 A A A A Feldthusen et al 30 A A A A Minnock et al 31 A A A A Mortada et al 32 A A A Nikolaus et al 33 A A A A Repping-Wuts et al 34 A A A A Thomsen et al 4 A A A CKD Cox et al 36 A A A A Kazemi et al 37 A A A A Monaro et al 38 A A Picariello et al 41 A A A A Pugh-Clarke et al 42 A A A A Schipper et al 39 A A A A Yngman-Uhlin et al 40 A A A A COPD Kouijzer et al 43 A A A A Paap et al 44 A A A Stridsman et al 45 A A A A Wortz et al 46 A A A A Shalit et al 47 A A A HF ¼ heart failure; MS ¼ multiple sclerosis; RA ¼ rheumatoid arthritis; CKD ¼ chronic kidney disease; COPD ¼ chronic obstructive pulmonary disease. The symbol 'A' denotes third-order themes included in the study.…”
Section: Studies By Chronic Conditionmentioning
confidence: 99%
“…Specifically, younger patients may need greater support, because they face the challenge of balancing HF disease restriction with finding a job or remaining employed, establishing meaningful relationships, attending to family duties, and maintaining financial security. 88 Finally, this study found that anxiety was associated with both pain and a history of comorbid depression. The association between body pain and anxiety has not been previously reported in research focusing on hospitalized or community patients with HF.…”
Section: Discussionmentioning
confidence: 65%